2009
DOI: 10.3746/jfn.2009.14.2.102
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Immunomodulatory Effects of β-Glucans from Yeast, Bacteria, and Mushroom on the Function of Macrophages

Abstract: The comparative immunomodulatory effects of β-glucans isolated from mushroom fungi (Coriolus versicol), yeast (Saccharomyces cerevisiae) and bacteria (Agrobacterium) on the major functions of macrophages were evaluated. As parameters of macrophage functions, we examined tumoricidal activity, phagocytosis, nitric oxide (NO) production, and the induction of inducible NO synthetase (iNOS) in RAW264.7 cells, following treatments with β-glucans from the three different sources. The results indicated that all β-gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…This indicates that giving PSK before and after exposure to P. aeruginosa affects on phagocytic activity which will eliminate the bacteria. This is supported by Jang et al (2009) that PSK has potential as a stimulator that can activate immunocompetent cells to increase the immune system.…”
Section: Phagocytic Activitymentioning
confidence: 72%
“…This indicates that giving PSK before and after exposure to P. aeruginosa affects on phagocytic activity which will eliminate the bacteria. This is supported by Jang et al (2009) that PSK has potential as a stimulator that can activate immunocompetent cells to increase the immune system.…”
Section: Phagocytic Activitymentioning
confidence: 72%
“…We suggested in the previous study that CVG showed stronger phagocytic activity than the ones from microorganism and seaweeds (Jang et al, 2009) and explained that its phagocytosis was promoted through Dectin-1 signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed comparable significant effects on phagocytosis and NO production in RAW264.7 macrophages by β-glucans from yeast, bacteria, and mushrooms, including C. versicolor, in vitro. Among them, β-glucans from C. versicolor (CVG) showed a highly significant effect on phagocytosis (Jang et al, 2009;Jang et al, 2010). Thus, we further studied the involvement of scavenger receptor class B1 (SR-B1) expression and its signaling in CVG-stimulated phagocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, ␤-glucan from mushrooms, C. versicolor (CVG), showed a highly significant effect on phagocytosis [15]. In present study, we focused on the intracellular molecular mechanisms of CVG and proposed a novel cellular signaling pathway in phagocytic effects.…”
Section: Introductionmentioning
confidence: 99%